Alginate and alginate/hyaluronic acid membranes generated by electrospinning in wet conditions: Relationship between solution viscosity and spinnability. Issue 25 (8th March 2018) - Vicini, Silvia; Mauri, Marco; Vita, Silvia; Castellano, Maila
ABSTRACT: The methodology to create alginate and alginate/hyaluronic acid membranes, which involves wet conditions electrospinning, is presented in this paper. The wet conditions allow simultaneously to work in water solutions avoiding the toxic solvents and to obtain crosslinked alginate. An accurate rheological characterization of all solutions examined is performed. By optimizing the electrospinning parameters, it is possible to obtain alginate membranes with homogeneous nanofibers and a narrow diameter distribution (i.e., around 100 nm) as well as alginate/hyaluronic acid membranes characterized by a network of bimodal distribution of the dimensions, namely nanofibers with a diameter comparable to the ones of the alginate membrane, in which are blocked microfibers with a ribbon like appearance, as observed in the SEM images. In order to facilitate the electrospinning process, poly(ethylene oxide) is added to the solutions and then removed after membranes preparation, as demonstrated by the differential scanning calorimetry results, obtaining membranes made up only biopolymers. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46390. Abstract :